Integrated Linguo-Subject Learning Foreign Language in a Medical University - Razikova Lola Tuychiyevna (Journal of Medical Genetics and Clinical Biology, 2024)
Integrated linguistic-subject training is one of the fundamental areas of higher professional education. Some aspects of integrated linguo-subject learning are considered. Examples of an integrated approach to teaching students of the Faculty of Medicine are presented.